Zainuddin Labay El Yunusy: Tokoh Pembaharuan Pendidikan Islam di Minangkabau Pada Awal Abad XX (Suatu Tinjauan Historis) - Syahril Syahril; Anggip Wilvon (Tarikhuna: Journal of History and History Education, 2022)
This research is motivated by the reform movement of Islamic education in Minangkabau at the beginning of the 20th century carried out by Zainuddin Labay el-Yunusy which has influenced modernization in Minangkabau which has had an impact to this day. This paper discusses the efforts made by Zainuddin Labay el-Yunusy in reforming Islamic education in Minangkabau in the early 20th century. This research is a library research using historical research methods consisting of heuristics, source criticism, interpretation and historiography by collecting primary and secondary sources from the literature. Zainuddin Labay el-Yunusy was born to Sheikh Muhammad Yunus al-Khalidiyah and Rafi'ah in 1890 in the Bukit Surungan district of Padang Panjang, coinciding with the 12th Rajab 1308 H and died on July 10, 1924 AD/8 Dzulhijjah 1342 H. Since childhood Zainuddin Labay was educated by his father who was also a scholar and then entered HIS, but did not graduate because he felt that he fit into the Dutch education curriculum. Furthermore, Zainuddin Labay studied with well-known educational figures in Minangkabau such as H. Rasul and Dr. Abdullah Ahmad in Padang. Zainuddin Labay has a very important role in reforming Islamic education in Minangkabau, among other things establishing the Diniyah School by incorporating general subjects into the Islamic education curriculum, fighting for the rights of Minangkabau women to obtain education, and forming a generation of Islam in Minangkabau. The reforms carried out by Zainuddin Labay towards Islamic education in Minangkabau inspired the establishment of modern Islamic education such as Diniyah Puteri Padang Panjang, changing the halaqah education system to become classical, and producing educational media. Keywords: Renewal, Islamic Education, Minangkabau.